2013
DOI: 10.1039/c3mt20261e
|View full text |Cite
|
Sign up to set email alerts
|

The use of X-ray absorption and synchrotron based micro-X-ray fluorescence spectroscopy to investigate anti-cancer metal compounds in vivo and in vitro

Abstract: X-ray absorption spectroscopy (XAS) and micro-synchrotron based X-ray fluorescence (micro-SXRF) are element specific spectroscopic techniques and have been proven to be valuable tools for the investigation of changes in the chemical environment of metal centres. XAS allows the determination of the oxidation state, the coordination motif of the probed element, the identity and the number of adjacent atoms and the absorber-ligand distances. It is further applicable to nearly all types of samples independent of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 144 publications
(228 reference statements)
0
44
0
3
Order By: Relevance
“…Scanning XRF microscopy has been used previously to reveal, for example, process-dependent alterations in bioelemental organization424344, including disease states45, and to study the pathways of heavy metal poisons4647. The often diffuse biodistribution of naturally occurring elements in these prior studies means that features, such as organelles and membranes can be poorly defined and ambiguity arises/would arise from use of these elements as labels, thereby hindering interpretation of associated maps.…”
Section: Discussionmentioning
confidence: 99%
“…Scanning XRF microscopy has been used previously to reveal, for example, process-dependent alterations in bioelemental organization424344, including disease states45, and to study the pathways of heavy metal poisons4647. The often diffuse biodistribution of naturally occurring elements in these prior studies means that features, such as organelles and membranes can be poorly defined and ambiguity arises/would arise from use of these elements as labels, thereby hindering interpretation of associated maps.…”
Section: Discussionmentioning
confidence: 99%
“…Synchrotron X-ray fluorescence (SXRF) imaging allows to examine the distribution of the different elements at the nanometer length scale [11]. Although some studies have shown that platinum is distributed homogeneously in whole and sectioned cells [14,15], other authors claim that this distribution varies depending on the cell type [16], and is related with the zinc content [17].…”
Section: Introductionmentioning
confidence: 99%
“…Such effect might imply a more efficient cisPt delivery within tumor cells and a higher protection of healthy cells. For that purpose, different particle acceleratorbased techniques, which have already demonstrated their potential in biological applications, are used [10][11][12]. In order to quantify the elemental concentration, the local mass particleinduced X-ray emission (PIXE) and backscattering spectrometry (BS) were performed simultaneously [13].…”
Section: Introductionmentioning
confidence: 99%
“…Synchrotron-based microfocused X-rayfluorescence (μ-SXRF) with microX-ray absorption near-edge structure (μ-XANES) or microXray diffraction (μ-XRD) are currently the most powerful set of techniques used for a complete characterization of biological samples. Among the set of techniques, μ-SXRF is very useful, allowing in situ mapping of nanoparticles with high sensitivity, negligible sample damage, and enable tuning of the incident energy as desired (Ma et al, 2011;Majumdar et al, 2012;Hernandez-Viezcas et al, 2013;Hummer and Rompel, 2013). Other promising advances include single particle inductively coupled plasma-mass spectrometry (spICP-MS), solid sampling highresolution-continuum source atomic absorption spectrometry (HR-CS AAS) and two-photon excitation microscopy (TPEM) (Wild and Jones, 2009;Feichtmeier and Leopold, 2013;Gray et al, 2013).…”
Section: Perspectives and Research Prioritiesmentioning
confidence: 99%